Zawarcie małżeństwa mieszanego wyznaniowo według prawa małżeńskiego z 1836 roku - Arkadiusz Fastyn (Czasopismo Prawno-Historyczne)
The thesis discusses the signifi cant question of inter-denominational marriages in Poland prior to 1946. Until the end of 1945, the laws in force in Poland were the 19th-century statutes. They had been enacted by the neighbouring countries (Austria, Russia and Prussia) that partitioned the Polish territory in the second half of the 18th century. In the Polish lands enjoying some autonomy in the Russian Empire, the regulation of marriage was based on the religious principles of 1836. Under the 1836 statute, there could be no civil marriage that would not produce a confessional effect. Consequently, the regulation of marriage had to combine confessional and civil effects into single norms and the legislative authorities had to provide for mechanisms correlating such effects. This applied to both the conclusion and dissolution of marriage. In these matters, the Roman Catholic Church adopted an uncompromising stance following from its belief in the special theological character of the sacrament of marriage.